Athlete Experiences of Shame and Guilt: Initial Psychometric Properties of the Athletic Perceptions of Performance Scale Within Junior Elite Cricketers - Rice, Simon M.; Treeby, Matt S.; Olive, Lisa; Saw, Anna E.; Kountouris, Alex; Lloyd, Michael; Macleod, Greg; Orchard, John W.; Clarke, Peter; Gwyther, Kate; Purcell, Rosemary (Frontiers in Psychology, 2021)
Guilt and shame are self-conscious emotions with implications for mental health, social and occupational functioning, and the effectiveness of sports practice. To date, the assessment and role of athlete-specific guilt and shame has been under-researched. Reporting data from 174 junior elite cricketers (M = 17.34 years; females n = 85), the present study utilized exploratory factor analysis in validating the Athletic Perceptions of Performance Scale (APPS), assessing three distinct and statistically reliable factors: athletic shame-proneness, guilt-proneness, and no-concern. Conditional process analysis indicated that APPS shame-proneness mediated the relationship between general and athlete-specific distress (p < 0.01), with this pathway non-contingent on sex or past 12-month help-seeking for mental health concerns (p's > 0.05). While APPS domains of guilt-proneness and no-concern were not significant mediators, they exhibited correlations in the expected direction with indices of psychological distress and well-being. The APPS may assist coaches and support staff identify players who may benefit from targeted interventions to reduce the likelihood of experiencing shame-prone states.